Climatic projections of lightning in southeastern Brazil using CMIP5 models in RCP’s scenarios 4.5 and 8.5 - Santos, Ana Paula Paes dos (2017)
Fil: Santos, Ana Paula Paes dos. National Institute for Space Research; Brazil.